Β-hydroxy-β-methylbutyrate supplementation in older persons – an update. Issue 1 (January 2021) - Bear, Danielle E.; Cruz-Jentoft, Alfonso J.; Stout, Jeffrey R.
Abstract : Purpose of review: The interest in the use of beta-hydroxy-beta-methylbutyrate (HMB) as an intervention to prevent and treat sarcopenia has increased over recent years. The purpose of this review is to explore recent evidence pertaining to the mechanism of action of HMB and how this may influence changes in lean mass and strength in older persons who are both hospitalized and living in the community. Recent findings: No new studies have been published over the last 2 years investigating the effect of HMB in older persons who are hospitalized, aside from one posthoc analysis of a randomized controlled trial exploring the effect of a high protein oral nutrition supplement containing HMB on handgrip strength and nutritional status. Three studies recruiting community-dwelling older adults have been published, but results are influenced by suboptimal methodological quality. Summary: Recent data suggest the need for high-quality studies investigating the effectiveness of HMB to improve outcomes related to sarcopenia in both hospitalized and community-dwelling older persons.